Wetlands : diversity and conservation status of vascular plants in Buenos Aires (Argentina) - Elisei, Aldana M.; Fischer, Maria De Los Angeles; Fortunato, Renee Hersilia; Bena, Julia (Sociedad Botánica Española, 2024)
Poster